Understanding the impacts of implementing AI writing digital tools on undergraduate students’ academic writing skills - Tan, Che Han (2025)
The use of Artificial Intelligence (AI) writing tools within higher education has become increasingly popular in terms of developing the quality of undergraduate students’ academic writing skills. This paper explores the effects of AI writing digital tools (e.g., Grammarly, ChatGPT, and Quillbot) on students’ performance in writing through a mixed-methods approach with 370 undergraduate-level surveys and semi-structured interviews. The results suggest that ease of use of the tool significantly predicts better writing skills and the need to make tools easy-to-use so as to promote engagement, while quality of feedback, writing anxiety and frequency of use are not statistically significant but rather optimistic for students. Qualitative results also confirmed that AI-tools supported immediate, non-judgmental feedback and less stress but higher confidence in writing, especially at the start of the task; however, questions were raised about generic outputs, fact-checking, lack of collaboration as well as ethical concerns around authorship. These findings have implications for writing education, as AI can help with superficial issues such as grammar, clarity, and surface fluency in writing, without reflective engagement and pedagogical mediation, the value of AI to develop deeper thinking (certainly critical thinking) and a developed argument is limited. The study indicates that AI tools require a balance with clear instructions, techniques and an ethical framework to utilize the effectiveness of AI tools in education and maintain academic integrity.